Profitability of maize for silage fertigated with nitrogen doses in different crops in a semiarid region of Brazil - Souza, Ênio Gomes Flôr; Cruz, Ellen Abreu da; Silva, Michelangelo de Oliveira; Barbosa de Souza Prates, Fabiano; Barros Júnior, Aurélio Paes; Bezerra Neto, Francisco (Acta Scientiarum. Agronomy, 2019)
The objective of this work was to determine the adequate nitrogen (N) dose via fertigation associated with the maximum economic production of maize for silage, in two agricultural crops (summer and winter), in the municipality of Canindé de São Francisco-SE, Brazil. The experimental design was in randomized blocks, with four replicates. The treatments consisted of four doses of N (0, 80, 160, and 240 kg ha-1) using urea. The cultivar planted was the hybrid Bt Feroz. The evaluated characteristics were as follows: shoot fresh and dry mass productivity, gross and net incomes, the rate of return and net profit margin. There was an interaction between N doses and agricultural crops for all variables. Higher agroeconomic efficiency in the production of maize for silage was obtained from the winter harvest. In the summer crop, the rate of return (1.82) and the net profit margin (45.52%) were highest when the plants were fertigated with 56.04 and 58.92 kg ha-1 of N, respectively. In winter, the yields of fresh mass, gross and net incomes increased linearly with increasing doses of N, with a profit proportional to the invested capital since nitrogen fertigation did not influence the rate of return (2.24) and the net profit margin (55.22%).